PENGEMBANGAN PENUNTUN PRAKTIKUM FISIKA DASAR 1 BERBASIS GUIDED INQUIRY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA - Nurussaniah Nurussaniah; Nurhayati Nurhayati (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This research aims to develop the Guide Practical Physics 1 based Guided Inquiry, knowing the quality of the Guide Practical Physics 1 based Guided Inquiry, study the response of the students after using the Guide Practical Physics 1 based Guided Inquiry and determine the increase critical thinking skills of students after using the Guide Practical Physics basic 1-based Guided Inquiry. This study is research & development (R & D) with Four-D Models, which consists of four phases: define, design, develop and disseminate. Stages of development used in this study is limited only to the stage of develo. Data collection techniques used in this study is the indirect communication techniques and measurement techniques. Based on the results, obtained a Basic Physics Practical Guidance 1-based Guided Inquiry. Quality Basic Physics Practical Guidance 1-based Guided Inquiry according to subject matter experts is 82%, and according to media expert is 87% , therefore Physics Practical Guidance 1-based Guided Inquiry is fit for use. Student response after using the Guide Basic Physics Lab 1 based Guided Inquiry categorized well with the percentage of 84%. Increasing students' critical thinking skills after using the Guide Basic Physics Lab 1 based Guided Inquiry is being categorized with the gain of 0.64.Keyword: Guide Lab, Guided Inquiry, Basic Physics 1